REKONSTRUKSI MEDIA PEMBELAJARAN VIDEO SCRIBE LISTRIK DINAMIS UNTUK SISWA KELAS XII SMA/MA - Zunafaroh, Risma; Putra, Ino Angga; Prihatiningtyas, Suci (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2020)
This study aims to determine the feasibility of learning media, students' mastery of concepts and scientific literacy. The research design uses the ADDIE development design. The feasibility of the media is seen based on the validation results of media experts and material experts. The results showed that the dynamic electric scribe video learning media that had been developed had the following characteristics: 1) the product validation test was obtained from the results of the media expert and material expert score of 3.67 with a proper classification. 2) the readability test was obtained from the results of the teacher response questionnaire and student responses of 3.58 with a proper classification. Based on the data above, it can be concluded that the Scribe video learning media is suitable for use as a physics learning medium.